Psychopharmacology of mania and schizophrenia - Leonard, Brian (Henry Stewart Talks, 2007)
Noradrenergic pathways in mania, Drugs used in the treatment of mania, Dopaminergic pathways in normal brain and in schizophrenia, Glutamatergic pathways in normal brain and in schizophrenia